The Impact of Religiosity on Psychological Well-Being Among Women Victims of Elephant Attacks - karjuniwati, karjuniwati; Zuanny, Iyulen Pebri; Nasruddin, Nasruddin; Safrilsyah, Safrilsyah; Muslim, Muslim; Alka, Muhammad; Wijayaningsih, Renita; Fuadi, Zahrul; Larasita, Puja (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2025)
Women who are victims of elephant attacks often experience fear in carrying out daily activities, impacting their psychological well-being. This study examines religiosity as a factor influencing their psychological resilience amid frequent elephant incursions into residential areas. The purpose of the research was to determine the effect of religiosity on the psychological well-being of these women. The study used religiosity and psychological well-being scales as measuring instruments, with purposive sampling and a total sample of 22 participants. Data were analyzed using simple linear regression, yielding a significant value of 0.013 (p < 0.05), indicating a significant effect. The R Square value was 0.271, meaning religiosity accounts for 27.1% of the variance in psychological well-being, while 72.9% is influenced by other factors. These findings highlight the important role of religiosity in helping women maintain psychological well-being despite the ongoing threat of elephant attacks.